Innovation Policy Reforms, Emerging Role Models and Bridge Institutions : Evidence from North African Economies - Djeflat, Abdelkader; Kuznetsov, Yevgeny (Taylor and Francis, 2015)
This article focuses on role models of modern innovation based development and public interventions to diffuse and scale up these role models. It discusses the so-called bridge institutions of innovation, which transform skills into knowledge valued by markets. It shows how these institutions (science and technology parks, international universities and skilled diaspora networks) promote innovation and create high productivity employment. Policy to promote innovation is, therefore, designed as a process with endogenous dynamics, where one-step follows the other and evolves in three time horizons: immediate (entry points), medium term (the critical mass effect) and long-term (major structural reforms). Case studies from North African countries indicate that entry points are numerous and more common than originally expected and that key issues are mostly linked to building critical mass in the medium term, and achieving structural reforms and cultural change in the long-term.